Modeling and compatibilization of projects of a residence My House My Life in BIM platform software (Research, Society and Development, 2019)
In the contractures and engeneer/architecture office, usually, there are big concernings to avoid interference between all the projects that comprise the edification planing. Thus, it’s necessary to do compatibilizations, that now in the days, most of the times, it’s achieved by the software autocad. Those compatibilizations are necessary, beacuse enable the reduction in the construction cost  in a way that not spend the money with new materials, manpower and rework. However, when the bim platform is used, provides a new experience, like agility in the work group to compatibilibilize with much better quality. This article have a goal to study the cases of the following projects: architecture, structure, hidrosanitary and eletric of a familiar residence program named my house my life, made by federal economic caixa, in software revit, as well as the incompatibilities identification between the projects quoted and the solutions, to make viable a new way of compatibilization to popular projects with better quality. The floor plane of the archtetonic project was inserted in revit software, to start the modeling, serving as the basis for the other projects. It was united in a fale the architectural and structural projects, and separated the hydrosanitary and eletric. The files were entered in the navisworks software to check for incompatibilities between the projects in the report.  The incompatibilities were found between electrical and hydraulic, hydraulic and structural and electrical and structural projects. Therefore, the bim platform is very necessary to identify the incompatibilities quickly and simply.